Diagnosis and Management of Eye Trauma in Primary Care Settings : A Systematic Review - Dinda Pebriani Simbolon; Vachroul Rauzi; Yuni Agnes Lubis (International Medical Journal Corp. Ltd, 2026)
Introduction: Eye trauma is a common presentation in primary care and emergency settings, yet guidance tailored to non-ophthalmologists remains fragmented. This review synthesises evidence on diagnosis, management, and triage of eye trauma to support primary care practitioners. Methods: A systematic review of 80 studies (2006–2026) including RCTs, etc. Populations included all ages with acute eye trauma. Outcomes focused on diagnostic accuracy, treatment efficacy, referral criteria, and visual outcomes. Results: Males predominate (62.8–99.3%) across all injury types. Corneal abrasions are the most common presentation (up to 80%). Topical NSAIDs reduce rescue analgesia (RR 0.46, p<0.01) but do not accelerate healing (1,2,3). Eye patching provides no benefit over no patching (4). Short-term topical tetracaine (24 hours) significantly reduces pain scores (NRS 1 vs 8, Δ7) without increased complications (5). Systemic tranexamic acid reduces secondary haemorrhage in traumatic hyphema (RR 0.31) (6). Point-of-care ultrasonography by non-ophthalmologists achieves 94% sensitivity and specificity for retinal detachment (7,8). Four independent predictors mandate urgent referral: visual acuity change, abnormal pupillary response, retrobulbar haemorrhage, and inability to open the eye (9,10,11). The Ocular Trauma Score correlates strongly with final vision (r=0.93) (12). Discussion: Primary care physicians demonstrate good inter-rater reliability versus ophthalmology when examinations are performed (sensitivity 60.6%, specificity 84.2%) (13). A substantial proportion of eye-related ED visits are non-urgent (39.5–53.5%) (14,15), indicating many cases are suitable for primary care. Cyanoacrylate tissue adhesive for periorbital lacerations in children achieves equivalent healing to sutures with shorter procedure time (184 vs 692 seconds) (16). Protective eyewear reduces firework injuries (OR 0.65) (17), and restrictive legislation reduces eye trauma by 87% (18). Conclusion: Most eye trauma can be managed safely in primary care using structured clinical assessment. Key positive findings include NSAIDs for pain, short-term topical anaesthetics for corneal abrasions, tranexamic acid for hyphema, and POCUS for posterior chamber evaluation. Four clinical predictors reliably identify patients needing urgent referral.